Archibald MacLeish - American Writers 99 : University of Minnesota Pamphlets on American Writers - Smith, Grover (Book collections on Project MUSE., 1972)
Archibald MacLeish - American Writers 99 was first published in 1971. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.